PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA PETANI PADI LADANG DI KECAMATAN SIDOMULYO KABUPATEN LAMPUNG SELATAN - Wardiah Nurul Khasanah; Ktut Murniati; Sudarma Widjaya (Lampung University, 2018)
The purposes of this research are to determine income of upland rice farming, income level of farmer household, and household welfare level of upland rice farming. This research was conducted in Sidomulyo Sub-district, South Lampung District. The location is determined purposively by consideration that Sidomulyo Sub-district is one of the rice producing centers with the highest number of upland rice farmers in South Lampung District. The number of respondents in this study was 54 farmers. The methods of analysis used in this research are descriptive qualitative and quantitative analysis. The results showed that it is unprofitable rice farming with R/C value over total cost of 0.69. The income of farmers in rice field that has the greatest contribution is on farm (cultivation of rice fields and corn farming) income with percentage of 54.74 percent of total household income. The household welfare level of upland rice farming according to poverty criteria by Sajogyo (1976) belongs to sufficient and by the World Bank belongs to not poor category. Key words: farm income, household income, household welfare, upland rice